International Cooperation in Educating and Training Police: Forwarding ASEAN’s Vision 2020 to Combat Non-Traditional Crimes - Luong, Hai Thanh (Advances in Social Sciences Research Journal, 2017)
This paper draws a detailed description of overall cross-border crimes that Southeast Asian region must be faced when forwarding one common communities on 2020. In order to improving capacity to preventing and combating non-traditional crimes, enhancing international cooperation in education and training for law enforcement agencies is considered as one of the priorities with the Association of Southeast Asian Nations (ASEAN) members. Thus, identifying effective models and professional opportunities in this field between Universities/Academies Police plays an important role in regional strategies to fighting transnational organized crime. To some extent, this study will divide into three main parts. Part one introduces briefly the ASEAN’s challenges and difficulties in dealing with non-traditional security and its forms of crime must be faced in integrated process with the worldwide. Part two gauges two basically current systems to police education and training around the world and its advantages and disadvantages. Finally, part three will discuss how about perspectives for international cooperation in training for law enforcement agencies to combating non-traditional crimes at ASEAN region in the future.